Comprehensive evaluation of compound Kushen injection combined with zoledronic acid in treating bone metastasis cancer pain based on meta-analysis and decision tree model - Xi Zhao; Tianwei Meng; Kaiqiang Wang; Xi Yan; Yuqiang Liu; Xinghua Li (Frontiers in Pain Research)
ObjectiveTo evaluate the safety, efficacy, and cost-effectiveness of combining Compound Kushen Injection (CKI) with zoledronic acid in the treatment of bone metastasis-induced cancer pain in malignant tumors.MethodsA comprehensive search of Chinese and English databases identified randomized controlled trials (RCTs) investigating CKI combined with zoledronic acid for bone metastases in malignancies. Methodological quality assessments were performed on all included studies, and a meta-analysis was conducted using RevMan 5.4.1 software. A cost-effectiveness analysis from the perspective of China's healthcare system employed a decision tree model to evaluate the short-term economic impact of the two treatment regimens. Sensitivity analyses assessed the robustness of the results.ResultsFourteen studies involving 1,269 patients were included in the meta-analysis. The results demonstrated that CKI combined with zoledronic acid was more effective than zoledronic acid alone in treating bone metastatic cancer pain (OR = 3.43, 95% CI: 2.51–4.67, P < 0.0001), with no significant difference in adverse reactions between the two groups. Incremental cost-effectiveness ratio (ICER) analysis revealed that the combination therapy incurred an additional cost of ¥18,863.16 for each unit of effect gained compared to zoledronic acid alone. Sensitivity analyses indicated stable results, showing that under the assumption of a willingness-to-pay threshold set at the average per capita disposable income in 2023, the combination of CKI and zoledronic acid was more cost-effective than zoledronic acid alone in treating bone metastatic cancer pain.ConclusionCompared with zoledronic acid alone, the combination of CKI and zoledronic acid offers superior efficacy, high safety, and better cost-effectiveness in the treatment of bone metastasis-induced cancer pain in malignant tumors.